Zwei Schweinchen sehen fern - Jörg, Sabine 1948-; Winterhager, Daniele 1953- (Schneider, 1987)
Schwipp and Schwapp, two young pigs, liked to play with their young human friend Sara until Farmer Bölte pput a television set in their field. Then they only watched TV and Sara was lonely.
Keywords: Friendship -- Fiction; German language materials; Swine -- Fiction; Television -- Fiction; Fernsehen; Schwein; Kinderbuch